Blast effects on buildings - Cormie, David; Mays, Geoffrey; Smith, P. D., 1950 March 26- (Thomas Telford Ltd., 2009)
Providing the latest practical guidance on designing buildings to optimise their resilience to blast loading, this text is focused specifically on the design of commercial buildings. It helps engineers reduce the risks posed to building occupants and businesses from terrorist and other explosions.